Keanekaragaman Fitoplankton Sebagai Indikator Kualitas Air Danau Sipin Di Kota Jambi - Guntar M Saragih; Winda Erizka (Universitas Batanghari Jambi, 2018)
Phytoplankton have an important role in a waters, as well as the base of the feed chain (primery producer) is also one of the parameters of the quality of a waters. This research was conducted for one day in November 2017 at Sipin Lake Jambi City on 3 (three) location points with survey and random sampling method. Abundance obtained with an average total of 2464 cells / L. The range of biological index values found is the index of diversity (H ') = 1,885-2,204. Physics-chemical parameters of instantaneous water are temperature 298C, turbidity 1,30-4,02 NTU, pH 6,39-6,71, BOD 2,42-2,82 mg / L, DO 4,41-5, 10 mg / L, nitrate 0,112-0,229 mg / L, and pospat 0,018-0,036 mg / L. The result of linear regression analysis and multiple correlation found that there is a very weak but correlation between physicochemical parameter of aquatic with phytoplankton abundance (r2 = 0,003) with regression equation Y = 2360,99 - 0,00005 temperature + 0,008 turbidity + 0,006 pH + 0,027 BOD + 0,036 DO + 0,226 nitrate + 0 pospat and have index value of saprobik (-1,625) which mean very heavy organic contamination or level of pollution class 4 (four) and fairness distribution (E) = 0,665-0,835 which means evenly. Keywords: Phytoplankton; Water Quality; Lake Sipin Water Jambi City; Relationship Level (Correlation).